Novel M tuberculosis Antigen-Specific T-Cells Are Early Markers of Infection and Disease Progression - (:unkn) unknown (PUBLIC LIBRARY SCIENCE, 2011)
Background: Mycobacterium tuberculosis Region-of-Difference-1 gene products present opportunities for specific diagnosis of M. tuberculosis infection, yet immune responses to only two gene-products, Early Secretory Antigenic Target-6 (ESAT-6) and Culture Filtrate Protein-10 (CFP-10), have been comprehensively investigated. Methods: T-cell responses to Rv3873, Rv3878 and Rv3879c were quantified by IFN-c-enzyme-linked-immunospot (ELISpot) in 846 children with recent household tuberculosis exposure and correlated with kinetics of tuberculin skin test (TST) and ESAT-6/CFP-10-ELISpot conversion over six months and clinical outcome over two years. Results: Responses to Rv3873, Rv3878, and Rv3879c were present in 20-25% of contacts at enrolment. Rv3873 and Rv3879c responses were associated with and preceded TST conversion (P = 0.02 and P = 0.04 respectively), identifying these antigens as early targets of cell-mediated immunity following M. tuberculosis exposure. Responses to Rv3873 were additionally associated with subsequent ESAT-6/CFP-10-ELISpot conversion (P = 0.04). Responses to Rv3873 and Rv3878 predicted progression to active disease (adjusted incidence rate ratio [95% CI] 3.06 [1.05,8.95; P = 0.04], and 3.32 [1.14,9.71; P = 0.03], respectively). Presence of a BCG-vaccination scar was associated with a 67% (P = 0.03) relative risk reduction for progression to active tuberculosis. Conclusions: These RD1-derived antigens are early targets of cellular immunity following tuberculosis exposure and T-cells specific for these antigens predict progression to active tuberculosis suggesting diagnostic and prognostic utility.
Keywords: PREDICTIVE-VALUE; IMMUNE-RESPONSES; ESAT-6 ANTIGEN; GENE-PRODUCTS; RD1 REGION; DIAGNOSIS; PROTEIN; ASSAY; BCG; EPITOPES